EF1025, a Hypothetical Protein From Enterococcus faecalis, Interacts With DivIVA and Affects Cell Length and Cell Shape - Sharma, Kusum; Sultana, Taranum; Liao, Mingmin; Dahms, Tanya E. S.; Dillon, Jo-Anne R. (Frontiers in Microbiology, 2020)
DivIVA plays multifaceted roles in Gram-positive organisms through its association with various cell division and non-cell division proteins. We report a novel DivIVA interacting protein in Enterococcus faecalis, named EF1025 (encoded by EF1025), which is conserved in Gram-positive bacteria. The interaction of EF1025 with DivIVAEf was confirmed by Bacterial Two-Hybrid, Glutathione S-Transferase pull-down, and co-immunoprecipitation assays. EF1025, which contains a DNA binding domain and two Cystathionine β-Synthase (CBS) domains, forms a decamer mediated by the two CBS domains. Viable cells were recovered after insertional inactivation or deletion of EF1025 only through complementation of EF1025 in trans. These cells were longer than the average length of E. faecalis cells and had distorted shapes. Overexpression of EF1025 also resulted in cell elongation. Immuno-staining revealed comparable localization patterns of EF1025 and DivIVAEf in the later stages of division in E. faecalis cells. In summary, EF1025 is a novel DivIVA interacting protein influencing cell length and morphology in E. faecalis.